The system of heuristic rules formation for network activity assessment - Корченко, Анна Олександрівна (Ukrainian Information Security Research Journal, 2013)
Based on the known method for anomalies detection caused by the cyberattacks the corresponding system has been developed. The implementation of this system requires the realization phase of multiple set of heuristic rules formation. They are intended to create the appropriating critical rules directed on truth verification of reference and current parameters interrelations when the network activity is being assessed in a specific environment. This paper suggests a new structural solution of the corresponding system based on the critical rules and containing switching units, the formation of linguistic variables, rules ranking and initialization, as well as registers of standards, current values, linguistic identifiers and rules. The proposed solution can be implemented through software or hardware and to be used as the basis of systems for anomalies detection.